1992
DOI: 10.1017/s0031182000061709
|View full text |Cite
|
Sign up to set email alerts
|

Dactylogyrus (Monogenea) communities on the gills of roach in three lakes in Central Finland

Abstract: SUMMARYDactylogyrus (Monogenea) species were studied on the gills of roach (Rutilus rutilus) from a total of 293 fish in 3 interconnected lakes in Central Finland. One of the lakes is eutrophic and polluted by a paper and pulp mill, one is eutrophic and one is oligotrophic. Nine Dactylogyrus species were found. The structure of the monogenean communities was analysed at the component and infracommunity level and the Dactylogyrus fauna of the lakes was compared. Although it was found that the component communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
23
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 18 publications
5
23
1
Order By: Relevance
“…For Buchmann (1989) and , the median preference arches may also be related to the large colonized surfaces they offer to parasites. Other factors such as parasite load (Lo and Morand, 2000) and the host immunity can also influence microhabitat selection (Koskivaara and Valtonen, 1992;Gutiérrez and Martorelli, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…For Buchmann (1989) and , the median preference arches may also be related to the large colonized surfaces they offer to parasites. Other factors such as parasite load (Lo and Morand, 2000) and the host immunity can also influence microhabitat selection (Koskivaara and Valtonen, 1992;Gutiérrez and Martorelli, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Parasites have been found to be associated with a deviance of symmetry in the development (MØLLER, 1992;POLAK, 1993;REIMCHEN, 1997, THOMAS et al, 1998, BROWN and BROWN, 2002but see also CLARKE, 1998and PALMER, 1999. This may be explained by (i) a direct stress caused by the metabolic cost of the parasite on its host (MØLLER, 1992;POLAK, 1993), (ii) a variation of the abundance of the parasite related to more or less stressful environmental conditions for hosts (KOSKIVAARA and VALTONEN, 1992), (iii) a relationship between the genetic incapacity to interfere with developmental errors and the susceptibility to parasite (MØLLER, 1996). Several studies have tested a relationship between FA and parasitism.…”
Section: Introductionmentioning
confidence: 99%
“…Moller 1987, Khan & Thulin 1991, Koskivaara & Valtonen 1992, Sures et al 1994a dealing with the interrelation between pollution and fish parasites, but there are just a few comparative, quantitative investigations about the heavy metal content of fish parasites and their hosts. Sures et al (1994a, b) reported very high lead concentrations in 2 species of palaeacanthocephalans.…”
Section: Introductionmentioning
confidence: 99%